A160 ESTIMATION OF FIBROSIS PROGRESSION RATES FOR CHRONIC HEPATITIS C: UPDATED META-ANALYSIS AND META-REGRESSION. (1st March 2018) - Erman, A; Hansen, T; Bielecki, J M; Feld, J; Krahn, M D; Thein, R
Abstract: Background: Chronic Hepatitis C viral infection (HCV) is a leading cause of cirrhosis, liver failure, and transplantation. The accurate estimation of HCV-disease progression is essential for evaluating the cost effectiveness of treatment and determining treatment prioritization. Aims: The purpose of this study was to obtain updated progression rate estimates (FPRs; i.e., pooled annual transition probabilities) of hepatic fibrosis in individuals with chronic HCV infection and to evaluate the impact of covariates on disease progression though an updated systematic review of the evidence, meta-analysis and meta-regression. Methods: A literature search was conducted using MEDLINE, EMBASE, and PubMed databases. The search covered a period of January 1990 to August 2014 with no language limit and was supplemented by reference and citation searches. In general, the review included peer-reviewed studies which examine hepatic fibrosis progression in HCV-infected individuals. Stage-specific annual transition probabilities (F0→1, F1→2 F2→3, F3→4 ) were estimated using the Markov Maximum Likelihood estimation method. Random-effects meta-analyses were used to pool FPRs. The impact of covariates on FPRs was explored through random effects meta-regression analyses. Time-to-cirrhosis was estimated using the pooled FPRs. Results: Overall, the systematic review included a total of 130 studies involving 160 groups of HCV-infected individuals (N=55, 581). The update contributed more subjects from non-clinical settings, injection drug users (IDUs), blood donor populations and genotype-1 and -3 infected groups. The pooled stage-specific FPRs were F0→1 : 0.113 (95%CI, 0.103–0.123); F1→2 : 0.087 (95%CI, 0.079–0.096); F2→3 :0.120 (95%CI, 0.110–0.131); F3→4 : 0.116 (95%CI, 0.105–0.128). Based on meta-regression analyses (Table 1 ), a longer duration of infection, and genotype-1 infection were independently associated with a slower progression, whereas male gender and blood transfusion were associated with faster progression with at least one FPR. Relative to liver clinic populations, pediatric and IDU populations also displayed a faster rate of progression for at least one transition rate. The estimated unadjusted time-to-cirrhosis was 37 years for all groups, 36 for patients identified in a clinical setting, 48 for non-clinical settings, 59 for genotype-1 and 30 years for genotype-3 groups. Conclusions: The current study provides updated estimates of FPRs associated with chronic HCV, explores covariates associated with progression and provides more precise progression estimates for specific patient populations. These estimates should allow for more accurate estimation of the cost-effectiveness of new HCV antivirals and alternative prevention strategies targeting different groups of patients. Funding Agencies: Canadian Network on Hepatitis C